Avaliação dos processos oxidativos avançados integrados ao processo biológico no tratamento de soro de queijo - Rocha, Amanda Carmelo da (2019)
Although it represents an important economic activity, the dairy industry is responsible for the generation of liquid effluents with high polluting potential and the disposal of cheese whey is one of its biggest problems. The aim of the present work was to improve the biodegradability of by-product cheese whey using combined treatments, in particular, coagulation/flocculation and advanced oxidative processes (AOPs), followed by anaerobic treatment. This cheese whey in natura came from an industry in the Minas Gerais triangle region. For its treatment, in addition to coagulation/flocculation using Chitosan, Tanfloc and processed papaya seed, the use of Fenton and photo-Fenton POAs was proposed. After these pre-treatments, it was submitted to an anaerobic treatment in Upflow Anaerobic Sludge Blanket (UASB) reactor. In the coagulation/flocculation stage, the influences of pH and natural coagulants were evaluated on the responses of total organic carbon (TOC), chemical oxygen demand (COD) and turbidity. At pH 10 and with coagulant seed of papaya processed (1 g/L), removals of 17.4% of TOC, 21.7% of COD and 95.5% of turbidity were achieved. The supernatant was redirected to the Fenton and photo- Fenton, where the influence of the concentrations of hydrogen peroxide and ferrous ion and iron were evaluated, considering removals of TOC, COD and residual hydrogen peroxide (H2O2). In the H2O2 concentration of 1.92 M, molar ratio H2O2/Fe2+ of 55 and reaction time of 90 min, removals of 62.2% TOC and 70.0% COD were obtained, without residual H2O2. The combined pre-treatment of cheese whey allowed the global removals around 76% COD, 64% TOC and 99% turbidity. Efficiency equivalent to the Fenton process was achieved by photo-Fenton in H2O2 concentration of 1.92 M, molar ratio H2O2/Fe2+ of 65 and reaction time of 60 min. The previously treated cheese whwy had its biodegradability increased (COD/BOD ratio 2.6 to 1.8). After 30 days of degradation in anaerobic reactor, COD removal was 87%. The cheese whey, after being submitted to the integrated coagulation flocculation treatments, photo- Fenton POA and anaerobic treatment, obtained an overall COD removal of 97%.